EXAMINING THE INTERSECTION OF GENDER, ENVIRONMENT, AND UNIVERSITY LEADERSHIP IN ADDRESSING CLIMATE CRISES - Hajra Maqsood Ali; Fakhra Aziz (International Journal of Contemporary Issues in Social Sciences, 2024)
The current research is pertinent due to the urgency of global changes in climatic patterns and emphasizes how important universities are as instruments for dealing with climate issues. Although the role of university leadership in establishing various environmental protection processes is well acknowledged in sustainable development, research has especially not addressed whether gender operates as an invisible or silent determinant that shapes these chameleonic leadership mechanisms and their corresponding responses/ approaches towards safeguarding the environment. Therefore, this paper reveals how gender the environment, and leadership in a university are intertwined with an environmental crisis being taken to pieces. Data were gathered using a qualitative method with semi-structured interviews of leaders in public universities (deans, directors, and heads of departments) from the region. The sample size was such that data saturation would be achieved and sufficient to represent the target population. Qualitative analysis was done using thematic analysis to understand the patterns and themes in the data collected. The coding was systematized under the following themes based on research questions. The themes that emerged were used to answer the questions from this study and make sense of all. These findings imply that they added to the existing literature highlighting how gender influences leadership practices and stances on environmental conservation. This article aims to provide pragmatic advice for administrators at institutions of higher education (IHE) interested in further disruptive efforts that will improve climate resilience on campus and nationally.